The frequency of psoriasis in Australian multiple sclerosis patients - Mangkorntongsakul, Varitsara; Fontes-Villalba, Ariadna; Montague, Turlough; Charlton, Olivia; Kwong, Chun-Ting Justin; McGuire, Helen Marie; Venkatesha, Venkatesha; Herkes, Geoffrey; Smith, Saxon; Parratt, John (Frontiers in Neurology, 2025)
BackgroundMultiple Sclerosis (MS) is an immune-mediated, demyelinating disease of the central nervous system. Although psoriasis and psoriasiform dermatitis are reported in MS patients, the prevalence of the diseases is uncertain globally and unstudied in Australia. This study aims to determine the frequency of psoriasis in a clinic-based cohort of Australian MS patients.MethodsA survey was conducted on 204 consecutive MS patients aged 18 and over who attended a tertiary MS clinic in Northern Sydney from July 2018 to December 2022.ResultsA total of 204 patients were examined, comprising 137 female (67.2%) and 67 male (32.8%). The mean age was 48.8 years (SD = 13.6). Psoriasis was identified in 13.7% (28/204; 95% CI: 9.63% to 19.20%).DiscussionThe frequency of psoriasis in MS is high and may be underestimated, given that many more patients have symptoms without signs. This implies an immunopathological link between the two conditions and is worthy of further study.